Establishment of local wastewater-based surveillance programmes in response to the spread and infection of COVID-19 – case studies from South Africa, the Netherlands, Turkey and England. (7th February 2022) - Tlhagale, M.; Liphadzi, S.; Bhagwan, J.; Naidoo, V.; Jonas, K.; van Vuuren, L.; Medema, G.; Andrews, L.; Béen, F.; Ferreira, M. L.; Saatci, A. M.; Alpaslan Kocamemi, B.; et al.
Abstract: The COVID-19 pandemic has resulted in over 340 million infection cases (as of 21 January 2022) and more than 5.57 million deaths globally. In reaction, science, technology and innovation communities across the globe have organised themselves to contribute to national responses to COVID-19 disease. A significant contribution has been from the establishment of wastewater-based epidemiological (WBE) surveillance interventions and programmes for monitoring the spread of COVID-19 in at least 55 countries. Here, we examine and share experiences and lessons learnt in establishing such surveillance programmes. We use case studies to highlight testing methods and logistics considerations associated in scaling the implementing of such programmes in South Africa, the Netherlands, Turkey and England. The four countries were selected to represent different regions of the world and the perspective based on the considerable progress made in establishing and implementing their national WBE programmes. The selected countries also represent different climatic zones, economies, and development stages, which influence the implementation of national programmes of this nature and magnitude. In addition, the four countries' programmes offer good experiences and lessons learnt since they are systematic, and cover extensive areas, disseminate knowledge locally and internationally and partnered with authorities (government). The programmes also strengthened working relations and partnerships between and among local and global organisations. This paper shares these experiences and lessons to encourage others in the water and public health sectors on the benefits and value of WBE in tackling SARS-CoV-2 and related future circumstances. HIGHLIGHTS: Designing and refining methodologies, epidemiological tools and indicators. Influencing public health decision-making through research data. Experiences on programme design and methodology for WBE surveillance. Partnerships strengthening communication and knowledge dissemination. Capacity building activities among the science communities, local authorities, industry nationally and internationally.